Psychology in sports coaching theory and practice - Nicholls, Adam R. (Routledge, Taylor & Francis Group, 2017)
Some of the most effective coaches understand the fundamentals of sport psychology, which include interacting effectively with athletes, creating the optimal environment, assessing the psychological needs of their athletes, and even providing them with the mental training required to maximise performance. Fully revised and updated, the second edition of Psychology in Sports Coaching: Theory and Practice clearly and accessibly introduces the principles and practice of sport psychology in the context of the coaching process. Drawing on the very latest research and theory, the book introduces the psychological tools and techniques that coaches can use to get the best performances out of their athletes.